Effective strategies dealing with construction cost overruns: a study in Jordan - Faten, Ahmad Al-Btoush (2021)
The success of the construction industry is the main goal of the stakeholders in any country since it improves the quality of life for individuals and the society. However, the Jordanian construction industries faces much challenges which lead to a decline of its contribution to GDP in the recent years. The construction industry in Jordan which is dynamic yet uncertain making cost management difficult, leading to cost overrun. For this reason, cost overruns have been considered as the critical factor during the construction life cycle. Serious attention is to be taken by the construction stakeholders to develop effective strategies to improve the cost performance. Past literature shows that most of the research mainly focuses on the factors of cost overruns while very few studies has been done to identify strategies to minimize the cost overrun in the construction projects. Thus, this study fills the gaps of research by identifying effective strategies to minimize the cost overrun in the construction projects. To achieve the research objectives, a mixture of quantitative and qualitative approaches for data collection which includes questionnaires, interviews with project managers, and focus group workshops has been adopted. All data collected were analyzed using SPSS software. The result from the questionnaires shows that critical causes of cost overruns are financial difficulties, materials and decisions, design issues and additional work. The interviews on the other hand, provides the strategies to minimize the cost overruns during different phases of project life cycle namely; project planning, design and construction. It is also observed that adoption of strategies to minimize cost overrun at the early stage of the project greatly minimize the cost overrun during the construction phase. On the other hand, the focus group workshop presents the effective strategies to minimize the seven critical factors of cost overruns namely frequent design changes, fuel cost increase, high transportation cost, payment problems faced by the contractor, owner's financial difficulties, payment problems faced by the client from the government, and extra quantity during construction. The finding confirms that the project owner plays an effective role in minimizing the cost overruns as the owner is the main source of funding for the project. Furthermore, the owner is also responsible for the selection of the designer, consultant and contractor. This research highlighted the critical phases of project life cycle that require sound planning and program to improve its efficiencies. Besides that, the result of this research provides sound knowledge of cost overrun and suggestions that would improve the project cost performance